ChemInform Abstract: Amino Azaxylylenes Photogenerated from o‐Amido Imines: Photoassisted Access to Complex Spiro‐Poly‐Heterocycles. Issue 5 (January 2016) - Mukhina, Olga A.; Kuznetsov, Dmitry M.; Cowger, Teresa M.; Kutateladze, Andrei G.
Abstract: The intramolecular photocyclization of amino azaxylylenes derived from o‐amido imines, e.g. compounds (I), (IV), and (VII), leads to mixtures of [4 + 4] and [4 + 2] adducts.